Histone Demethylase LSD1 Promotes Adipocyte Differentiation through Repressing Wnt Signaling. Issue 10 (20th October 2016) - Chen, Yan; Kim, Jeesun; Zhang, Ruipeng; Yang, Xiaoqin; Zhang, Yong; Fang, Jianwu; Chen, Zhui; Teng, Lin; Chen, Xiaowei; Ge, Hui; Atadja, Peter; Li, En; et al.
Summary: Adipose tissue plays important roles in animals. White fat stores energy in lipids, while brown fat is responsible for nonshivering thermogenesis through UCP1-mediated energy dissipation. Although epigenetic mechanisms modulate differentiation in multiple lineages, the epigenetic regulation of brown adipocyte differentiation is poorly understood. By screening a collection of epigenetic compounds, we found that Lysine-Specific Demethylase 1 (LSD1) inhibitors repress brown adipocyte differentiation. RNAi-mediated Lsd1 knockdown causes a similar effect, which can be rescued by expression of wild-type but not catalytic-inactive LSD1. Mechanistically, LSD1 promotes brown adipogenesis by demethylating H3K4 on promoter regions of Wnt signaling components and repressing the Wnt pathway. Furthermore, deletion of Lsd1 in mice leads to inhibition of brown adipogenesis, validating the pivotal role of LSD1 in brown fat development in vivo. Our work identifies LSD1 as a key epigenetic regulator in brown adipogenesis. The link between LSD1 and the Wnt pathway provides potential opportunities to modulate brown fat differentiation. Graphical Abstract: Highlights: Four epigenetic chemical probes are identified in a BAT differentiation screen LSD1 inhibition or depletion blocks the differentiation of brown adipocytes LSD1 demethylates H3K4 on Wnt pathway genes and downregulates their transcription LSD1 knockout in newborn mice leads to brown fat defects Abstract : Chen et al. identified LSD1 inhibitor and other epigenetic compounds as brown adipogenesis modulators. LSD1 enables the repression of Wnt signaling by demethylating H3K4 on the promoter of Wnt pathway genes, and thereby promoting brown fat differentiation.